Composition for modulating immune system and preparation method thereof - Mohamed, Suhaila; Abu Bakar, Nurul Ain; Anyanji, Victor Uchenna; Abdullah, Maha; Mohamed Mustapha, Noordin (2012)
The present invention to provide a composition for modulating the immune system with no adverse or side effects. In accordance with one aspect of the present invention, there is provided a composition for modulating the immune system, the composition comprising extracts of Palmae, algae and Morinda. The present invention also provides use of a composition comprising Palmae, algae and Morinda extracts in the manufacture of therapeutic agent for modulating immune system.